EXPLORING IMPACT OF K-POP CELEBRITY WORSHIP ON WELL-BEING AND SELF-EFFICACY OF YOUNG ADULTS IN FCSHD - Najah Khaliqah, Abdul Khalid (Universiti Malaysia Sarawak, (UNIMAS), 2022)
K-Pop has become the global phenomenon in the past decade. K-pop fans can be found easily these days as the emerging of fast-paced internet and technologies. This qualitative study aims to explore the impacts of K-pop celebrity worship on the young adults’ well-being and self-efficacy. Through semi-structured interviews, the participants experiences while doing celebrity worship are explored as well as the factors that causes them to be a K-pop fans are also explored. This study has found that the factors that cause young adults to be a K-Pop fans are music genre, messages in the music, appreciation of hard work, K-pop contents and appearance. K-pop celebrity worship have given positive impact towards the young adults’ well - being. The impact of celebrity worship on the young adults’ self-efficacy has benefitted them in a way of increasing their self-efficacy.